2013
DOI: 10.3390/ijms140816168
|View full text |Cite
|
Sign up to set email alerts
|

Post-Transcriptional Regulation by Poly(ADP-ribosyl)ation of the RNA-Binding Proteins

Abstract: Gene expression is intricately regulated at the post-transcriptional level by RNA-binding proteins (RBPs) via their interactions with pre-messenger RNA (pre-mRNA) and mRNA during development. However, very little is known about the mechanism regulating RBP activities in RNA metabolism. During the past few years, a large body of evidence has suggested that many RBPs, such as heterogeneous nuclear ribonucleoproteins (hnRNPs), undergo post-translational modification through poly(ADP-ribosyl)ation to modulate RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 97 publications
2
65
0
1
Order By: Relevance
“…However, it is not clear how the translational machinery in the posterior pole is able to bypass the repression posed by the TCE structure, which is sufficient to inhibit nos translation (39). Recent studies have shown that poly-(ADP-ribosyl)ation of the RNA-binding proteins can modulate the RNA-binding ability for controlling the posttranscriptional events (53)(54)(55)(56). Indeed, our present data showed that poly(ADPribose) can disrupt the interaction between Hrp38 and the nos 3= UTR, enhancing nos translation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear how the translational machinery in the posterior pole is able to bypass the repression posed by the TCE structure, which is sufficient to inhibit nos translation (39). Recent studies have shown that poly-(ADP-ribosyl)ation of the RNA-binding proteins can modulate the RNA-binding ability for controlling the posttranscriptional events (53)(54)(55)(56). Indeed, our present data showed that poly(ADPribose) can disrupt the interaction between Hrp38 and the nos 3= UTR, enhancing nos translation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…19,[95][96][97][98][99] All these regulatory functions can be achieved via the basic enzymatic activity of PARP1, which is involved in post-translational modification of specific proteins. PARP1 catalyzes the attachment of multiple chains of ADP ribose [poly (ADP) ribose; PAR] from NAD to target (acceptor) proteins, and the main acceptor is PARP1 protein itself.…”
mentioning
confidence: 99%
“…Отсутствие коилина, напротив, сопровождается ослаблением/выключением этого механизма, способствуя накоплению вирусной РНК до уровней, которые могут потенциально насытить механизм РНКинтерференции, что позволяет преодоле вать его действие в системных листьях ТРkd. Согласно нашим данным, ядерным белком, вовлеченным в коилин зависимый ответ на вирусную инфекцию, может быть поли(АДФрибозо) полимераза (PARP1), выполняющая важную роль в толерантности организма к генотоксиче скому стрессу, репарации ДНК, транскрипции, контроле клеточного цикла и клеточных ответах на биотический и абиотический стрессы, включая процессы, относящиеся к механизму программируемой клеточной смерти (Kotova et al, 2009;Briggs, Bent, 2011;Bassett, 2012;Luo, Kraus, 2012;Ji, Tulin, 2013;Schulz et al, 2014). Этот белок осу ществляет свои регуляторные функции путем специфи ческой модификации (АДФрибозилирования) отдельных белков и автомодификации.…”
Section: роль ядра и ядерных белков в устойчивости растений к вирусамunclassified